Aberrant Methylation of Thrombospondin-1 and Its Association with Reduced Expression in Gastric Cardia Adenocarcinoma. (15th March 2010) - Guo, Wei; Dong, Zhiming; He, Ming; Guo, Yanli; Guo, Jianwen; Chen, Zhifeng; Yang, Zhibin; Kuang, Gang
Abstract : Aim . Investigate the promoter methylation of the Thrombospondin-1 (TSP1) gene in gastric cardia adenocarcinoma (GCA). Methods . MSP approach, immunohistochemistry method, and RT-PCR were used respectively to examine the promoter methylation of TSP1, its protein and mRNA expression in tumors and corresponding normal tissues. The expression and concentration of TGF-β 1 were examined respectively by immunohistochemistry and ELISA method. The status of T cell immunity was examined by Flow cytometry analysis. Results . TSP1 was methylated in 34/96 (35.4%) tumor specimens, which was significantly higher than that in corresponding normal tissues (P < .001 ). Protein and mRNA expression of TSP1 in GCA tumor tissues were reduced significantly and were associated with TSP1 methylation. The protein expression of TGF-β 1 was significantly higher in tumor tissues (P < .001 ) and was associated with TNM stage and histological differentiation. The concentration of active and total TGF-β 1 did not show significant difference between the GCA patients with hypermethylation of TSP1 and without methylation of TSP1 (P > .05 ). The function of T cell immunity was significantly different between the GCA patients with hypermethylation of TSP1 and without methylation of TSP1. Conclusions . Epigenetic silencing of TSP1 gene by promoter hypermethylation may play an important role in GCA.